1988
DOI: 10.1063/1.454314
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies of the radiative properties of the N2+2 D 1Σ+u state

Abstract: Articles you may be interested inExperimental and theoretical studies of the structural and electronic properties of vanadium-benzene sandwich clusters and their anions: V n Bz n 0/− (n = 1-5) and V n Bz n− 1 0/− (n = 2-5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…After 1s photoionization the monocationic system emits an Auger electron, resulting in a valence doubly ionized N 2+ 2 . It is well known that certain N 2+ 2 electronic states support vibrational resonances in which the molecular dication can stay bound for long times of up to seconds [5,[22][23][24][25]. Measurements of the yield of N 2+ 2 as a function of pump-probe delay have shown that after x-ray absorption and Auger decay, the IR pulse enhances the fragmentation of N 2+ 2 , as evidenced by a clear yield reduction.…”
Section: Introductionmentioning
confidence: 99%
“…After 1s photoionization the monocationic system emits an Auger electron, resulting in a valence doubly ionized N 2+ 2 . It is well known that certain N 2+ 2 electronic states support vibrational resonances in which the molecular dication can stay bound for long times of up to seconds [5,[22][23][24][25]. Measurements of the yield of N 2+ 2 as a function of pump-probe delay have shown that after x-ray absorption and Auger decay, the IR pulse enhances the fragmentation of N 2+ 2 , as evidenced by a clear yield reduction.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The molecular nitrogen dication ͑N 2 2+ ͒ is of particular interest because of the high abundance of nitrogen in the terrestrial atmosphere and, partly because of this, the electronic states of the N 2 2+ ion have been widely investigated both experimentally and theoretically. 5,[38][39][40][42][43][44][45][46][47][48] The contribution of molecular dications to the properties of planetary ionospheres has generally been assumed to be insignificant. However, a recent prediction of a CO 2 2+ layer in the ionosphere of Mars 7 has implied that dications, and processes involving dications, may have more significance than previously thought in the upper atmospheres of planets.…”
Section: Introductionmentioning
confidence: 99%
“…This state fluoresces in transitions to the N ++ 2 ground state, with bands centred around 159 nm (Table 6). The fluorescence lifetime of the N ++ 2 D 1 + u electronic state is 6.0±0.5 ns, according to Olsson et al (1988). No collisional deactivation is therefore liable to occur in the ionosphere during this very short lifetime.…”
Section: Fluorescencementioning
confidence: 99%
“…For O ++ 2 , Avakyan (1978b) also reports the possible identification of auroral emissions around 243 nm which he ascribes to the A 3 + u -X 1 + g transition: despite the fact that no further confirmation of a fluorescence feature in O ++ 2 has yet been found, three emission wavelengths have recently been tabulated by Avakyan (1998), as shown in Table 6, where we list the fluorescence transitions and their respective wavelengths for N The N () excited state of specific interest to us is D 1 + u , which lies 7.8 eV above the N ++ 2 ground state (Ahmad, 2002;Olsson et al, 1988). This state fluoresces in transitions to the N ++ 2 ground state, with bands centred around 159 nm (Table 6).…”
Section: Fluorescencementioning
confidence: 99%
See 1 more Smart Citation